COMMUNITY EMPOWERMENT ANALYSIS TOWARDS A PROSPEROUS BARENGKRAJAN VILLAGE COMMUNITY - Pradana, Hepy Oktavianto; Sutinem; Handayati, Ratna; Syairozi, Muhamad Imam (Ecopreneur.12, 2025)
The study aims to analyze the community empowerment program and analyze the implementation of the community empowerment program in Barengkrajan Village. The researcher applied the triangulation method to get answers to the research questions. The findings show that the empowerment program carried out in Barengkrajan Village is very effective. The village implements the One Village One Product (OVOP) program so that the program carried out can be maximized and more effective by adding value (product differentiation) from the program that has been carried out.